Small Magnets, Big Future: Low-Field MRI Technology and Clinical Utility - Mohamamdreza Elhaie; Abolfazl Koozari; Iraj Abedi; Mahmoud Mohammadi-Sadr; Abbas Monsef (Frontiers in Biomedical Technologies)
Purpose: Despite the clinical advances made in magnetic resonance imaging with high static magnetic fields (1.5T and more), open MRI with low field (0.2-0.5T) has recently attracted the attention of researchers.